Anxiety Confronted by EFL Students in Instructional Listening Class - Erna Iftanti; Joko Tri Prastiyo (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The barrier of learning listening is experienced by students that make them feel anxious. Consequently, it easily effects their performance during listening class. Therefore, this study is aimed to describe the anxiety types and causes of anxiety confronted by EFL students in listening class at university level. To accomplish this aim, Qualitative research designs was applied by the researchers. The research subjects were English Department Students in IAIN Tulungagung. The research data were obtained through observation in listening class and in-depth interviews to the six most anxious informants. Then, the collected data was analyzed by data reduction, data presentation, and conclusion drawing. In order to check trustworthiness of data, theoretical and methodological triangulations applied. The result of this study was revealed that there were six symptoms of anxiety confronted by the students in listening class, that were categorized as the type of Arousal Anxiety (ArA), Apprehension Anxiety (ApA), and Mixed Anxiety (MA) also revealed five causes of anxiety. Those results inform the lecturer to be understood about students’ anxiety and start to create the joyful learning in listening class so that they are more comfortable following the class.